2018
DOI: 10.1021/acs.macromol.8b01981
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Crystalline Polyperoxides from Fatty Acid Containing Styrenic Monomers

Abstract: Vinyl polyperoxides, alternating copolymers of vinyl monomers and molecular oxygen, are highly viscous amorphous materials because of the flexible peroxy (−O− O−) bonds in the main chain. In this study, crystalline polyperoxides have been synthesized by oxidative radical polymerization of styrenic monomers having fatty acid moieties attached to the phenyl ring using molecular oxygen at 100 psi pressure. Determination of active oxygen contents in polyperoxides, 13 C NMR spectroscopy, and electron impact mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Crystalline behavior of n‐alkyl methacrylate based polymers having number of side chain alkyl carbons C ≥ 12 was established by Hempel et al Polyperoxides from 4‐vinylbenzyl fatty esters showed crystalline behavior when the fatty acid moieties had alkyl chains with C ≥ 12 . In the present study, we determined the effect of MMA content on the crystalline behavior of the copolyperoxides from VBS and MMA monomers.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Crystalline behavior of n‐alkyl methacrylate based polymers having number of side chain alkyl carbons C ≥ 12 was established by Hempel et al Polyperoxides from 4‐vinylbenzyl fatty esters showed crystalline behavior when the fatty acid moieties had alkyl chains with C ≥ 12 . In the present study, we determined the effect of MMA content on the crystalline behavior of the copolyperoxides from VBS and MMA monomers.…”
Section: Resultsmentioning
confidence: 68%
“…MMA (Sigma, 99%) was purified just before the polymerization reaction, by passing through an alumina oxide column to remove inhibitors. Side‐chain SA containing monomer 4‐vinylbenzyl stearate (VBS), was synthesized following previously reported literature . The 2,2′‐azobisisobutyronitrile (AIBN, Sigma, 98%) was purified from methanol by recrystallization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyperoxides, which include a labile OO bond in their main-chain repeating unit, are produced from vinyl and conjugated diene monomers in the presence of molecular oxygen by a conventional radical alternating copolymerization process. 1,2 Due to a readily degradable nature, the polyperoxides have been applied to various degradable functional materials such as dismantlable adhesives, 36 drug delivery system, 7 biodegradable materials, 8 fatty acid-containing crystalline polymers, 9 and property changeable thin films. 10,11 The polyperoxides obtained from sorbic esters have a highly regular chain structure consisting of an exclusive 5,4-unit as the alternating repeating diene unit (Figure 1(a)).…”
mentioning
confidence: 99%
“…PP-CPD and PP-Fu readily degraded upon heating with a significant exothermic heat evolution, which is typically observed for polyperoxides. 9,12,14 The 5% weight loss temperature (T d5 ) and the maximum decomposition temperature (T max ) were T d5 = 129°C and T max = 169°C for PP-CPD, and T d5 = 88°C and T max = 133°C for PP-Fu. These values are approximately in the temperature Figure 5.…”
mentioning
confidence: 99%